The Relationship Between Night Shift Work and the Risk of Abnormal Thyroid-Stimulating Hormone: A Hospital-Based Nine-Year Follow-up Retrospective Cohort Study in Taiwan - Hsin-Hao Chen; Hsiao-Hui Chiu; Tzu-Lin Yeh; Chi-Min Lin; Hsin-Yi Huang; Shang-Liang Wu (Elsevier, 2021)
Background: Health-care providers typically undergo shift work and are subjected to increased stress. Night shift work may induce disturbed sleep cycles and circadian rhythm. The objective of this study was to explore if night shift workers (NSWs) show an increased risk of abnormal thyroid-stimulating hormone (TSH). Methods: We conducted a retrospective cohort study of 574 employees without thyroid disease and abnormal TSH at baseline who underwent annual check-ups between 2007 and 2016 in a medical center. NSWs were defined as those with working time schedules other than daytime hours. We calculated the incidence rate and estimated the adjusted hazard ratio (HR) for incident abnormal TSH and subclinical hypothyroidism compared with non-NSWs using a Cox regression model. Results: A total of 56 incident abnormal TSH cases and 39 subclinical hypothyroidism cases in NSWs were identified during 3000 person-years of follow-up. In models adjusted for age, sex, obesity, and working departments, we found no increased relative risk for incident abnormal TSH (HR: 0.72, 95% confidence interval: 0.33-1.60) or subclinical hypothyroidism (HR: 0.52, 95% confidence interval: 0.19-1.45) when comparing NSWs to non-NSWs; nor were incidence rates significantly different among exclusively medical employees after excluding administrative staff. Conclusion: In this hospital-based nine-year follow-up retrospective cohort study, NSWs were not associated with increased relative risk of incident abnormal TSH and subclinical hypothyroidism, in contrast to previous cross-sectional studies.